Pengujian pada Aplikasi "Kembaliin" Berbasis Mobile Application/Android dengan Metode Design Thinking - Retno Wulandari; Firli Nurdiansyah; Mochamad Hasbani; Alif Yoga Prasetya; Teti Desyani (Jurnal Informatika Universitas Pamulang, 2020)
With the development of information and communication technology. Users and actors in IT (Information Technology) are increasingly spoiled with gadgets that are easier in terms of function and protection. A smartphone is a function similar to a PC or notebook with an easy-to-carry operating system and mobile application. A smartphone will usually be equipped with a separate operating system / OS. At this time the most famous operating system is Android is a search engine giant, namely Google. Before we make we need to design the application that we made, so that the user understands and easily uses the application created